PENGEMBANGAN E-LKPD ETNOMATEMATIKA BERBASIS PROJECT BASED LEARNING (PjBL) UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA - Anggraini, Putri; Anggoro, Bambang Sri; Muhammad, Rosida Rakhmawati (De Fermat : Jurnal Pendidikan Matematika, 2026)
The study is a Research and Development (R&D) study employing the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation), which aims to develop an ethnomathematics-based electronic student worksheet (E-LKPD) integrated with Project Based Learning (PjBL) to improve students’ critical thinking skills, which are still low in mathematics learning, particularly at SMA Negeri 5 Bandar Lampung. Data were collected through expert validation questionnaires, attractiveness questionnaires, and critical thinking skills tests. The validation results indicate that the E-LKPD is considered feasible based on the material expert assessment with an average score of 3.82 and the media expert assessment with a score of 3.65. Students’ responses in the small-scale and large-scale trials obtained scores of 3.2 and 3.5, respectively, categorized as very attractive, indicating that the integration of ethnomathematics in the Project Based Learning (PjBL)-based E-LKPD enhances students’ learning interest. Furthermore, the effectiveness test based on the N-Gain calculation resulted in a score of 0.51 in the moderate category, indicating that the E-LKPD is sufficiently effective. Therefore, the ethnomathematics-based E-LKPD integrated with Project Based Learning (PjBL) is feasible, attractive, and effective in improving students’ critical thinking skills.